2020
DOI: 10.3390/ijerph17061965
|View full text |Cite
|
Sign up to set email alerts
|

Are Physical Education Lessons Suitable for Sport Talent Identification? A Systematic Review of the Literature

Abstract: Objectives: The goal of this study was to shed light on the existent knowledge, internationally published over the last decade (2009–2019), on how to deal with talented children in physical education (PE). Methods: A mixed systematic review (SR) was conducted following Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines and registered in the International Prospective Register of Systematic Reviews (PROSPERO), registration number: CRD42019117211. Study eligibility criteria: Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 64 publications
0
7
0
Order By: Relevance
“…The study is significant, as it provides the first known systematic review of the literature on the identification and development of physical giftedness/talent. Related reviews of the literature have had a narrower focus, specifically on talent identification in sport or physical education (Johnston et al, 2018;Prieto-Ayuso et al, 2020). By providing an overview of the existing intellectual territory in the area (relating to a period of time that simultaneously captures the greatest portion of the research in the area, and the most recent period, and therefore the most relevant period, to inform future work), it is expected that this review will draw attention to the precise scope of existing knowledge and its strengths/ deficiencies, to set some clear directions for research and as a basis from which to move the area forward.…”
Section: Significance Of the Studymentioning
confidence: 99%
“…The study is significant, as it provides the first known systematic review of the literature on the identification and development of physical giftedness/talent. Related reviews of the literature have had a narrower focus, specifically on talent identification in sport or physical education (Johnston et al, 2018;Prieto-Ayuso et al, 2020). By providing an overview of the existing intellectual territory in the area (relating to a period of time that simultaneously captures the greatest portion of the research in the area, and the most recent period, and therefore the most relevant period, to inform future work), it is expected that this review will draw attention to the precise scope of existing knowledge and its strengths/ deficiencies, to set some clear directions for research and as a basis from which to move the area forward.…”
Section: Significance Of the Studymentioning
confidence: 99%
“…The advent of 'war for talent' as proclaimed by McKinsey decades ago in the early 21 st century raised the profile of talent in the strategic agenda or organizations as well as in education institutions in the world (Van, Mathafena & Ras, 2015). Indeed, it is emerging that enlisting talented persons in organizations has been a key preoccupation for institutional managers in this century more than at any given time in human history ( Van et al, 2015;Renström & Stenling, 2019;Prieto-Ayuso et al, 2020). However, potentially valuable human talent will be wasted if society does not pay attention to understanding how that talent develops and how it should be managed.…”
Section: Introductionmentioning
confidence: 99%
“…As an integral part of education, PE is a purposeful, planned, and organized educational process conducted through physical activities and other auxiliary means (Mountakis, 2001 ). In a systematic review, Prieto-Ayuso et al ( 2020 ) showed that methods and instruments for talent identification in PE are changing, so it is important to select appropriate programs to deal with gifted children. In addition, PE teachers in the development of the scale can help speed up the identification of potential talents (Platvoet et al, 2015 ); however, teachers in school PE still face certain difficulties within the identification process (Bailey et al, 2009 ).…”
Section: Introductionmentioning
confidence: 99%